Analysis of Individualized Training Stimulates Women’s Work Potential - Guan, Ke (Transactions on Economics, Business and Management Research, 2024)
At present, many enterprises still have problems in the training implementation process such as single training content, lack of pertinence and flexibility, resulting in the actual needs of female employees be fully met. The discussion of individualized training model can provide more suitable career development path for female employees and promote their all-round development in the workplace. This not only contributes to the promotion of women’s personal career, but also brings certain help for enterprises to cultivate high-quality talents and enhance their overall competitiveness. According to the collected literature, the personality characteristics, advantages and expertise of female employees are analyzed, and customized training programs are combined to help female employees effectively improve their professional ability and comprehensive quality. Personalized training can empower female employees to leverage their strengths in the workplace, leading to enhanced team cohesion, improved team collaboration efficiency, attention to work details, and strengthened user experience. In order to recognize the value of female employees’ personal growth in achieving professional success. This article proposes that when designing employee training, companies should tailor the content to the specific strengths and gender-related advantages of female individuals. To empower female employees to fully acknowledge their potential and strengths in the workplace, clarify their career development pathways, facilitate their rapid growth and breakthroughs, and ultimately achieve the objective of unlocking their work potential while assisting them in realizing their professional aspirations.